Dynamic modelling and validation of tracked vehicle with in-track motor - Noor Amira Ilyanie Ruslan,; Noor Hafizah Amer,; Nurulhani Adlina Madzan,; Khisbullah Hudhab,; Zulkiffli Abd. Kadir,; Syed Mohd Fairuz Syed Mohd Dardin,; Saiddi Ali Firdaus Mohamed Ishak, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper addresses dynamic modelling and validation of a tracked vehicle, as well as provides an in-depth examination of an in-track DC motor system. The characteristics of the DC motor will be rigorously assessed, providing a foundational understanding to enhance vehicle control and mobility. Furthermore, an independent DC motor controller will be developed through an inverse model database of its characteristics. The model validation process will involve various trajectory types, including right and left turns. The real vehicle was equipped with an Arduino Mega and MPU6050 accelerometer sensor, along with the DC motor controller unit. Data acquisition was developed by integrating Arduino and the MATLAB/Simulink simulation environment. The proposed model was validated by evaluating the Root Mean Square (RMS) of the percentage error between the values of the experiment and the model prediction. It was found that, for right and left turns of the vehicle, the percentage error produced is below 12.7% which shows the model is able to follow the path in real conditions, providing a foundation for future advancements in transportation and autonomous technology.